Permeability Enhancement Properties of High-Pressure Abrasive Water Jet Flushing and Its Application in a Soft Coal Seam - Zhang, Xinzhe; Wiśniewski, Piotr; Dykas, Sławomir; Zhang, Guojie (Frontiers in Energy Research, 2021)
High-pressure abrasive water jet flushing (HPAWJF) is an effective method used to improve coal seam permeability. In this study, based on the theories of gas flow and coal deformation, a coupled gas-rock model is established to investigate realistic failure processes by introducing equations for the evolution of mesoscopic element damage along with coal mass deformation. Numerical simulation of the failure and pressure relief processes is carried out under different coal seam permeability and flushing length conditions. Distributions of the seepage and gas pressure fields of the realistic failure process are analyzed. The effects of flushing permeability enhancement in a soft coal seam on the gas drainage from boreholes are revealed by conducting a field experiment. Conclusions can be extracted that the gas pressure of the slotted soft coal seam is reduced and that the gas drainage volume is three times higher than that of a conventional borehole. Field tests demonstrate that the gas drainage effect of the soft coal seam is significantly improved and that tunneling speed is nearly doubled. The results obtained from this study can provide guidance to gas drainage in soft coal seams regarding the theory and practice application of the HPAWJF method.